Pedagogy of the implicated: advancing a social ecology of responsibility framework to promote deeper understanding of the climate crisis. (27th May 2022) - Bryan, Audrey
ABSTRACT: This paper draws on Deborah Britzman's conceptualisation of 'difficult knowledge' and Michael Rothberg's figure of 'the implicated subject' to advance a Social Ecology of Responsibility Framework (SERF) in relation to the climate crisis.This framework demonstrates the impossibility of disarticulating individual, private actions that contribute to the ecological crisis from state-corporate climate-related harms. While not discounting differences of scale between individual actions and state-corporate crimes, the article highlights difficulties with binaristic approaches to climate responsibility which privilege either  personal actions  or  macro-level norms, practices and ideologies. Foregrounding self-implication, the model serves as a basis for establishing transnational and transgenerational solidarity with human and other-than-human lifeforms who inhabit the Earth. The paper concludes with some examples of visual images and accompanying activities that can be used to prompt critical reflection on one's own positioning as an implicated subject and as a change agent who can contribute to the amelioration of global warming.